Principles of distributed database systems - Özsu, M. Tamer 1951-; Valduriez, Patrick; SpringerLink (Online service). (New York Springer, 2011)
This third edition of a classic textbook can be used to teach at the senior undergraduate and graduate levels. The material concentrates on fundamental theories as well as techniques and algorithms. The advent of the Internet and the World Wide Web, and, more recently, the emergence of cloud computing and streaming data applications, has forced a renewal of interest in distributed and parallel data management, while, at the same time, requiring a rethinking of some of the traditional techniques. This book covers the breadth and depth of this re-emerging field. The coverage consists of two parts. The first part discusses the fundamental principles of distributed data management and includes distribution design, data integration, distributed query processing and optimization, distributed transaction management, and replication. The second part focuses on more advanced topics and includes discussion of parallel database systems, distributed object management, peer-to-peer data management, web data management, data stream systems, and cloud computing. New in this Edition: New chapters, covering database replication, database integration, multidatabase query processing, peer-to-peer data management, and web data management. Coverage of emerging topics such as data streams and cloud computing. Extensive revisions and updates based on years of class testing and feedback Ancillary teaching materials are available.
Introduction -- Background -- Distributed Database Design -- Database Integration -- Data and Access Control -- Overview of Query Processing -- Query Decomposition and Data Localization -- Optimization of Distributed Queries -- Multidatabase Query Processing -- Introduction to Transaction Management -- Distributed Concurrency Control -- Distributed DBMS Reliability -- Data Replication -- Parallel Database Systems -- Distributed Object Database Management -- Peer-to-Peer Data Management -- Web Data Management -- Current Issues -- References -- Index.
Electronic reproduction.
Keywords: Distributed databases; Electronic books